2013
DOI: 10.1111/dom.12076
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic characteristics of lixisenatide once daily versus liraglutide once daily in patients with type 2 diabetes insufficiently controlled on metformin

Abstract: AimAssess the pharmacodynamics of lixisenatide once daily (QD) versus liraglutide QD in type 2 diabetes insufficiently controlled on metformin.MethodsIn this 28-day, randomized, open-label, parallel-group, multicentre study (NCT01175473), patients (mean HbA1c 7.3%) received subcutaneous lixisenatide QD (10 µg weeks 1–2, then 20 µg; n = 77) or liraglutide QD (0.6 mg week 1, 1.2 mg week 2, then 1.8 mg; n = 71) 30 min before breakfast. Primary endpoint was change in postprandial plasma glucose (PPG) exposure from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
213
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(240 citation statements)
references
References 38 publications
(70 reference statements)
16
213
1
10
Order By: Relevance
“…Our data thus lend support to the theory that incretin‐based therapies (and GLP‐1 receptor agonists in particular) appear well‐suited for use in Asian and Japanese patients with T2D,28, 30 as these populations are predisposed to insulin deficiency rather than insulin resistance, which may manifest via a profound underlying GLP‐1 insufficiency 40. The findings of the present study are also consistent with studies in Western patients with T2D inadequately controlled on metformin or on optimized Gla‐100, as once‐daily pre‐breakfast lixisenatide was associated with significantly greater reductions in PPG, postprandial C‐peptide, and postprandial glucagon relative to pre‐breakfast liraglutide 31, 32. Gastric emptying was also substantially slower in the lixisenatide than the liraglutide study group 31, 32…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our data thus lend support to the theory that incretin‐based therapies (and GLP‐1 receptor agonists in particular) appear well‐suited for use in Asian and Japanese patients with T2D,28, 30 as these populations are predisposed to insulin deficiency rather than insulin resistance, which may manifest via a profound underlying GLP‐1 insufficiency 40. The findings of the present study are also consistent with studies in Western patients with T2D inadequately controlled on metformin or on optimized Gla‐100, as once‐daily pre‐breakfast lixisenatide was associated with significantly greater reductions in PPG, postprandial C‐peptide, and postprandial glucagon relative to pre‐breakfast liraglutide 31, 32. Gastric emptying was also substantially slower in the lixisenatide than the liraglutide study group 31, 32…”
Section: Discussionsupporting
confidence: 88%
“…Lixisenatide was associated with a pronounced improvement in postprandial hyperglycaemia compared with placebo in these studies,25, 26, 27, 29 including studies in Asian patients exclusively 28, 30. Further, lixisenatide had a greater postprandial effect on blood glucose levels than the longer‐acting GLP‐1 receptor agonist liraglutide in patients with T2D insufficiently controlled on metformin, with or without insulin glargine 31, 32…”
Section: Introductionmentioning
confidence: 86%
“…The shorter-acting GLP-1 receptor agonists (GLP-1RAs) exenatide and lixisenatide are of particular interest because of their ability to blunt postprandial glycemic increments (mainly by slowing gastric emptying) while also potentiating endogenous insulin secretion and suppressing inappropriate elevations of glucagon (21)(22)(23)(24)(25). Studies have shown that these agents, when used in combination with basal insulin and metformin, can flatten the postprandial glucose profile without increasing the risks of hypoglycemia and weight gain often associated with prandial insulin treatment (26)(27)(28)(29).…”
mentioning
confidence: 99%
“…The half-life of subcutaneously administered GLP-1 agonists appears to dictate whether efficacy is primarily preprandial ('non-prandial') or postprandial ('prandial'). 'Prandial' agonists (exenatide, lixisenatide) have a short duration of action, exerting a greater effect on postprandial glycaemia, predominantly through potent slowing of gastric emptying and postprandial insulin suppression [55].…”
Section: Potential Future Researchmentioning
confidence: 99%